2020
DOI: 10.26675/jabe.v4i2.6622
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Attitude Toward Money on Students’ Financial Literacy and Financial Behavior

Abstract: This research aims at discovering the direct influence of financial literacy on financial behavior; finding out the indirect influence of financial literacy on financial behavior through attitude toward money; and figuring out the direct influence of attitude toward money on financial behavior. This research was conducted at Economics Faculty of State University of Semarang or UNNES with its sample being students who had taken budgeting and financial management courses. The sample was taken using proportionate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 10 publications
1
6
0
3
Order By: Relevance
“…The study demonstrated that H1, which states that “financial literacy” has a significant positive influence on financial risk tolerance, is supported. The results of this study advance existing research on financial literacy, 5 , 66 , 67 by projecting that financial literacy stimulates financial risk tolerance of investors, allowing them to make more robust and sound financial decisions. The results of this analysis are in harmony with previous studies.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The study demonstrated that H1, which states that “financial literacy” has a significant positive influence on financial risk tolerance, is supported. The results of this study advance existing research on financial literacy, 5 , 66 , 67 by projecting that financial literacy stimulates financial risk tolerance of investors, allowing them to make more robust and sound financial decisions. The results of this analysis are in harmony with previous studies.…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, our third hypotheses state that (a) financial literacy has a significant positive relationship with financial behavior, and (b) financial risk tolerance mediates the relationship between financial literacy and financial behaviour. By investigating financial risk tolerance as the mediating mechanism, our study attempts to bridge the omission in the direct link between financial literacy and financial behavior, 66 , 67 which turn out to be our unique contribution in this study. We come back to its theoretical implications in the subsequent section.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As soon as they are admitted to a university, most students become responsible for their own finances, but because of a lack of parental supervision, they are more inclined to spend than to manage their money (Susilowati et al., 2020). The purchase of clothes, shoes, and other fashion accessories appears to be a common form of consumerism among these students (Susilowati et al., 2020). As a result, the ability to face financial challenges and make sensible financial decisions is an important skill for university students to learn.…”
Section: Introductionmentioning
confidence: 99%
“…There are reports showing that a growing number of students have continued to struggle with huge debts because they lack a working understanding of financial literacy and lack the tools required to make the best financial decisions (e.g., Draper, 2019; Fox, 2021). The university student population is currently a major market for financial products and services; in spite of this, students’ poor financial literacy continues to prevent them from fully utilizing these products and services (Susilowati et al., 2020). Inadequate financial literacy impacts a person’s ability to save for long-term goals and their day-to-day attitudes toward money (Zucchi, 2022).…”
Section: Introductionmentioning
confidence: 99%